2016
DOI: 10.1016/j.lithos.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous mantle of the Congo craton: Evidence from mineral and fluid inclusions in Kasai alluvial diamonds

Abstract: Alluvial diamonds from the Kasai River, Katanga Province, Democratic Republic of the Congo (DRC), were studied in order to constrain the composition, thermal state, and diamond forming fluids of the ancient lithospheric mantle of the Congo craton. The diamonds originate from Cretaceous kimberlites of the Lucapa graben in northeastern Angola. We report carbon isotope compositions (δ 13 C VPDB ), nitrogen concentrations ([N]), and nitrogen aggregation states of 138 diamonds, as well as compositions of mineral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Silicic to low-Mg carbonatitic compositions were reported from the Kaapvaal craton Kempe et al 2021a;Weiss unpublished data), the Congo craton (Navon et al 1988;Kopylova et al 2010;Kosman et al 2016;Timmerman et al 2019), the West African craton (Weiss et al 2009), the Amazonian craton (Shiryaev et al 2005), the Slave craton (Klein-BenDavid et al 2007;Logvinova et al 2008b;Weiss et al 2015), the North Atlantic craton (Elazar and Weiss 2021), India , and the Siberian craton Zedgenizov et al 2009Zedgenizov et al , 2011Skuzovatov et al 2016;Gubanov et al 2019). The Siberian HDFs have the most extreme compositions on both ends of the silicic to low-Mg carbonatitic array, with SiO 2 both >65 and <15 wt% (on a carbonate-and water-free basis; Figs.…”
Section: Silicic To Low-mg Carbonatitic Hdfsmentioning
confidence: 96%
“…Silicic to low-Mg carbonatitic compositions were reported from the Kaapvaal craton Kempe et al 2021a;Weiss unpublished data), the Congo craton (Navon et al 1988;Kopylova et al 2010;Kosman et al 2016;Timmerman et al 2019), the West African craton (Weiss et al 2009), the Amazonian craton (Shiryaev et al 2005), the Slave craton (Klein-BenDavid et al 2007;Logvinova et al 2008b;Weiss et al 2015), the North Atlantic craton (Elazar and Weiss 2021), India , and the Siberian craton Zedgenizov et al 2009Zedgenizov et al , 2011Skuzovatov et al 2016;Gubanov et al 2019). The Siberian HDFs have the most extreme compositions on both ends of the silicic to low-Mg carbonatitic array, with SiO 2 both >65 and <15 wt% (on a carbonate-and water-free basis; Figs.…”
Section: Silicic To Low-mg Carbonatitic Hdfsmentioning
confidence: 96%
“…Its general crystal‐chemical formula is commonly represented as X 3 Y 2 Z 3 O 12 , where Z are tetrahedral sites mostly occupied by Si 4+ ; Y are octahedral cation sites, usually filled with Al 3+ , Fe 3+ and Cr 3+ ; X cations are coordinated by eight oxygen atoms and can accommodate Mg 2+ , Fe 2+ , Ca 2+ , Mn 2+ , and so on. Eclogites incorporated as xenoliths in eruptive rocks from global major ultrahigh‐pressure metamorphic (UHPM) belts and kimberlites indicate that eclogitic garnets are mainly composed of pyrope (Prp, Mg 3 Al 2 Si 3 O 12 ), almandine (Alm, Fe 3 Al 2 Si 3 O 12 ) and grossular (Grs, Ca 3 Al 2 Si 3 O 12 ) with very few other end‐member garnets like spessartine (Sps, Mn 3 Al 2 Si 3 O 12 ) and andradite (Adr, Ca 3 Fe 3+ 2 Si 3 O 12 ; e.g., Kosman et al, ; Ren et al, ; Taylor et al, ; Wang, ; Wang et al, ; Weber & Bucher, ). In addition, some eclogitic garnets generally contain ~1 wt.% of TiO 2 (e.g., Stachel & Harris, ; Wang et al, ), which could be neglected in that case, although some studies reported garnets with high Ti content (Wang et al, ), in which case the present model may not be applicable.…”
Section: Introductionmentioning
confidence: 99%
“…For the Congo craton, diamond-bearing eclogites were suggested in Catoca pipe [121]. However, the largest data set for the diamond inclusions was published for the alluvial deposits of the Kasai River, NE Angola [120].…”
Section: Congo Cratonmentioning
confidence: 99%